Digital water : enabling a more resilient, secure and equitable water future - Sarni, William (Earthscan water text, 2022)
"This book shows how digital technologies are transforming how we locate, manage, treat, distribute and use water. Water resources are under stress from over-allocation, increased demand, pollution, climate change and outdated public policies. Historical approaches to delivering water for human consumption, industrial production, agriculture, power generation and ecosystems are no longer adequate to meet demands. As a result, we need to vastly improve the efficiency and effectiveness of our public and private sector processes in water management. The author describes recent advances in data acquisition (e.g., satellite imagery, drones and on the ground sensors and smart meters), big data analytics, artificial intelligence and blockchain, which provide new tools to meet needs in both developing and developed economies. For example, a digital water technology portfolio brings the value of real-time system-wide monitoring - and response - within the capability of water providers of all sizes and sophistication. As such, digital water promises to increase the long-term value of water resource assets while assisting in compliance with regulations and helping respond to the demands of population growth and evolving natural and business ecosystems. Including many practical examples, the author concludes that digital and smart water technologies will not only better manage water assets, but also enable the public sector to provide universal access to safe drinking water, the private sector to continue to grow and ecosystems to thrive"--